Amino Acid Changes at Arginine 204 of Troponin I Result in Increased Calcium Sensitivity of Force Development - Nguyen, Susan; Siu, Rylie; Dewey, Shannamar; Cui, Ziyou; Gomes, Aldrin V. (Frontiers in Physiology, 2016)
Mutations in human cardiac troponin I (cTnI) have been associated with restrictive, dilated and hypertrophic cardiomyopathies. The most commonly occurring residue on cTnI associated with familial hypertrophic cardiomyopathy (FHC) is arginine (R), which is also the most common residue at which multiple mutations occur. Two FHC mutations are known to occur at cTnI arginine 204, R204C and R204H, and both are associated with poor clinical prognosis. The R204H mutation has also been associated with restrictive cardiomyopathy (RCM). To characterize the effects of different mutations at the same residue (R204) on the physiological function of cTnI, six mutations at R204 (C, G, H, P, Q, W) were investigated in skinned fiber studies. Skinned fiber studies showed that all tested mutations at R204 caused significant increases in Ca2+ sensitivity of force development (∆pCa50 = 0.22-0.35) when compared to wild-type (WT) cTnI. Investigation of the interactions between the cTnI mutants and WT cardiac troponin C (cTnC) or WT cardiac troponin T (cTnT) showed that all the mutations investigated, except R204G, affected either or both cTnI:cTnT and cTnI:cTnC interactions. The R204H mutation affected both cTnI:cTnT and cTnI:cTnC interactions while the R204C mutation affected only the cTnI:cTnC interaction. These results suggest that different mutations at the same site on cTnI could have varying effects on thin filament interactions. A mutation in fast skeletal TnI (R174Q, homologous to cTnI R204Q) also significantly increased Ca2+ sensitivity of force development (∆pCa50 = 0.16). Our studies indicate that known cTnI mutations associated with poor prognosis (R204C and R204H) exhibit large increases in Ca2+ sensitivity of force development. Therefore, other R204 mutations that cause similar increases in Ca2+ sensitivity are also likely to have poor prognoses.